2006
DOI: 10.1080/09593332708618655
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Landfill Leachate by Irrigation and Interaction with Landfill Gas

Abstract: The treatment efficiency of landfill leachate irrigation and the effect of landfill gas addition were investigated in a vegetated compost/gravel substrate by monitoring soil moisture content, drainage water volume and quality in a two years lysimeter experiment. Landfill leachate irrigation exceeding 350 mm increased soil moisture and drainage volumes owing to the deterioration of the vegetation resulting from high sodium chloride inputs. Even so sodium chloride was lost in between the irrigation periods, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
6
1
1
Order By: Relevance
“…Therefore, irrigation regimes closer to IRR1 than IRR3 would be preferable in clay soils grown with willow, considering the high nutrient concentrations, particularly of organic N, in the leachate. On the other hand, the absolute concentrations of NH 4 -N and total P in the drainage water for treatment IRR3 for willow were not high compared with reported values Jonsson et al, 2004;Watzinger et al, 2006), whereas TOC and Cl concentrations were relatively high compared with previous findings. All the above suggest that the quality of landfill leachate is highly important in minimising environmental risks.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Therefore, irrigation regimes closer to IRR1 than IRR3 would be preferable in clay soils grown with willow, considering the high nutrient concentrations, particularly of organic N, in the leachate. On the other hand, the absolute concentrations of NH 4 -N and total P in the drainage water for treatment IRR3 for willow were not high compared with reported values Jonsson et al, 2004;Watzinger et al, 2006), whereas TOC and Cl concentrations were relatively high compared with previous findings. All the above suggest that the quality of landfill leachate is highly important in minimising environmental risks.…”
Section: Discussioncontrasting
confidence: 79%
“…Scientific studies on the treatment efficiency of such systems show promising results but variable efficiency (Alker, 2002;Dimitriou et al, 2006;Watzinger et al, 2006). Studies from the UK have reported toxicity symptoms in willow plants irrigated by landfill leachate, probably due to its high ionic strength (Stephens et al, 2000).…”
Section: Introductionmentioning
confidence: 96%
“…Estimated total leaching losses of NO 3 –N (Table 7) amounted to approximately 53% of the NH 4 –N + NO 3 –N applied during the 4 yr of this study. Watzinger et al (2006) also found that 44% of the nitrogen applied in landfill leachate, as measured by drainage from zero‐tension lysimeters, was leached as NO 3 –N. In contrast, Bowman et al (2002) reported much lower NO 3 –N leaching from spray‐irrigated leachate (7–11% of N applied), largely as a result of management of their system to encourage denitrification.…”
Section: Resultsmentioning
confidence: 98%
“…In our study, increased biomass on leachate‐treated areas served as an effective erosion control measure and helped to maintain the integrity of the landfill cover. Excessive applications of high‐conductivity leachate, however, can cause the vegetative cover to deteriorate (Hernandez et al, 1999; Bowman et al, 2002; Jones et al, 2006, Watzinger et al, 2006), reducing its effectiveness as part of the treatment system.…”
Section: Resultsmentioning
confidence: 99%
“…Similar systems have been tested in the UK, USA, Poland and elsewhere (Bialowiec et al, 2007;Godley et al, 2004;Jones et al, 2006;Zalesny and Bauer, 2007). Some scientific studies on the treatment efficiency of such systems show promising results but variable efficiency (Alker, 1999;Dimitriou et al, 2006;Watzinger et al, 2006). Studies from the UK have reported toxicity symptoms in willow plants irrigated by landfill leachate, probably due to its high ionic strength (Stephens et al, 2000).…”
Section: Introductionmentioning
confidence: 97%